ANALISIS PENGARUH KECEPATAN PEMOTONGAN MESIN CNC CUTTING PLASMA TERHADAP DIMENSI AKHIR DAN KEKASARAN PERMUKAAN PADA BAJA AH36 - Susilo, Trisno; Fazly Arliansyah, Muhammad (Fakultas Sains dan Teknologi Universitas Karimun, 2024)
This study aims to determine the effect of cutting speed on several variables, namely the final dimensions of the cutting results, time efficiency, and surface roughness using CNC Plasma Arc Cutting. This study used an experimental method on cutting AH36 steel with a thickness of 11 mm with a cutting speed of 3000 mm/min, 4000 mm/min, 5000 mm/min. Surface roughness testing was carried out using a visual test. The results showed that the lower the cutting speed, the less accurate the final dimensions were due to the long cutting flame hitting the material and vice versa. The greater the cutting speed, the faster the cutting is done. . The higher the cutting speed, the rougher and untidy the surface roughness. The lowest accuracy value is 3 mm x 3 mm with a cutting speed of 3000 mm/min, while the highest accuracy is 3 mm x 1.5 mm with a cutting speed of 5000 mm/min. The most efficient cutting speed is using a speed of 5000 mm/min with a completion time of 9.12 seconds.